Osteosarcoma in Pregnancy - Pravin Nepal; G K Singh; M P Singh; S Bajracharya; G P Khanal; S R Pandey (Journal of Nepal Medical Association, 2005)
Osteosarcoma in pregnant women is rare. Delay in diagnosis may be due to lack of any signs or symptoms during gestation, clinical misdiagnoses, religious attitude and refusal of the patients. Most cases soft-tissue and bone tumors during pregnancy can be managed successfully with surgery during gestation. Therapies with fetal toxicity were more likely to be deferred to postpartum period. This case is rare and liable to be missed, hence is reported.